Fractal Dimension of Random Attractors for Non-Autonomous Fractional Stochastic Reaction-Diffusion Equations (Journal of Partial Differential Equations, 2020)
"This paper deals with non-autonomous fractional stochastic reaction-diffusion equations driven by multiplicative noise with $s \u2208 (0,1).$ We first present some\u00a0 conditions for estimating the boundedness of fractal dimension of a random invariant set. Then we establish the existence and uniqueness of tempered pullback random attractors. Finally, the finiteness of fractal dimension of the random attractors is proved."
Keywords: Random dynamical system; random attractor; fractal dimension; fractional reaction-diffusion equation; multiplicative noise.